2021
DOI: 10.1186/s12882-021-02560-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between glomerular IgG staining and poor prognostic findings in patients with IgA nephropathy: the data from TSN-GOLD working group

Abstract: Background Galactose-deficient IgA1 (Gd-IgA1) has an increased tendency to form immunocomplexes with IgG in the serum, contributing to IgAN pathogenesis by accumulating in the glomerular mesangium. Several studies showed that glomerular IgG deposition in IgAN is an important cause of mesangial proliferation and glomerular damage. This study aims to determine the association of the positivity of IgG and the intensity of IgG staining with a poor renal prognosis. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some researchers have investigated whether the intensity of IgG staining could have an impact on the kidney outcomes in IgAN. In one study, no correlation was found between the intensity of IgG staining and various clinical parameters and Oxford scores in IgAN [ 20 ]. A Japanese cohort study reported an opposite conclusion that the intensity of IgG in the capillary loops was associated with a decrease in eGFR [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have investigated whether the intensity of IgG staining could have an impact on the kidney outcomes in IgAN. In one study, no correlation was found between the intensity of IgG staining and various clinical parameters and Oxford scores in IgAN [ 20 ]. A Japanese cohort study reported an opposite conclusion that the intensity of IgG in the capillary loops was associated with a decrease in eGFR [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of multivariate logistic regression analysis demonstrated that the intensity of IgG deposition was associated with a poorer prognosis of the disease. This suggests that the severity or intensity of IgG deposition in the glomeruli may have an impact on the progression of IgAN and could be considered as a prognostic factor [ 20 ]. The greater potential of IgG deposits to initiate and sustain an inflammatory process may accelerate the progression of IgAN.…”
Section: Discussionmentioning
confidence: 99%